The Structuring and Empowerment Policy of Losari Beach Street Vendors Based on The Concept of Smart City. Issue 1 (November 2021) - Ahdi, P S; Akil, A; Ramli, M
Abstract: Mining activities in open pit and underground mines will always be associated with rock breaking or stripping activities (both mechanical and blasting), so that this can affect the structure and strength of rocks. The strength of the rock is strongly influenced by the presence of initial cracks (pre-existing cracks) and rock anisotropy conditions associated with discontinuous plane conditions. Fracture mechanics is a science that illustrates how a fracture can occur and propagate during applied stress on material. The main parameter in fracture mechanics is called fracture toughness which shows the resistance of the material to propagate the crack. There are several mode in determining type I fracture toughness, one of which is type I fracture toughness Flattened Brazilian Disc (FBD) mode. Type I fracture toughness test is carried out using a compression machine in a laboratory and is conducted on concrete samples consisting of 3 (three) various samples, with a ratio of cement and sand composition of 1:1, 1:2, and 2:1. This test also uses different loading rate values, namely 2.50 mm/min, 2.70 mm/min, and 2.83 mm/min. The results of the type I fracture toughness value from each loading rate will be compared to determine the effect of the loading rate on the value of type I fracture toughness. The obtained fracture toughness value is also related to the physical and mechanical properties of the samples. Based on the results of tests, it can be seen that the loading rate affects the value of fracture toughness, the increase in fracture toughness value is followed by the higher loading rate. In addition, it can be seen that the fracture toughness value is directly proportional to the uniaxial compressive strength value and the indirect tensile strength value. The average correlation value obtained is R 2 = 0.9884 (indicating a strong relationship).